Early Cretaceous riparian vegetation in Patagonia, Argentina - Cladera, Gerardo (2007)
Early Cretaceous riparian vegetation in Patagonia, Argentina. An autochthonous plant as-semblage found at the Bajo Grande locality, Anfiteatro de Ticó Formation, Baqueró Group, Early Aptian of Santa Cruz province, Argentina, is described. Sedimentological data show an alternation of sandstone and lime-stone, with recurrent fossil levels associated to a fluvial system. The frequent flood in areas close to the levee had an influence on the vegetation growing along the banks of the channels. A plant assemblage composed of Ricciopsis grandensis nov. sp. (bryophyte), Adiantopteris tripinnata nov. sp., Schizaeaceae pinnules (ferns), and the gnetalean fructification Ephedra verticillata nov. sp. was found in this paleoenvironment. The taphonomical studies suggest that the plant assemblage was autochthonous, and it grew and was buried in an area near a levee. This result is congruent with environmental data provided by living representative of the fossil taxa analyzed.